Does regular quality control improve the quality of surgery in Slovenian breast cancer screening program? - Perhavec Andraz; Milicevic Sara; Peric Barbara; Zgajnar Janez (Radiology and Oncology, 2020)
The aim of our study was to evaluate the quality of surgery of Slovenian breast cancer screening program (DORA) using the requested EU standards. Furthermore, we investigated whether regular quality control over the 3-year period improved the quality of surgical management.